Reformulation of Rehabilitation Sanctions for Perpetrators of Sexual Violence Crimes - I Gusti Bagus Yoga Sastera; I Gusti Bagus Suryawan (Jurnal Hukum Prasada, 2024)
This research aims to explore the best way to reconstruct rehabilitation sanctions for perpetrators of sexual violence. The formulation of the problems raised in this study are first: why perpetrators of sexual violence need to be rehabilitated and which perpetrators of sexual violence can be subject to rehabilitation punitive measures and what kind of rehabilitation, Second: how to reformulate the best sanctions against sexual violence in the future (ius constituendum) to make it more effective. The type of research used by the author is normative research. The results of this study suggest that perpetrators of sexual violence should be rehabilitated if certain conditions require rehabilitation measures, such as sexual deviation. However, it should be noted that the implementation of rehabilitation measures must be very selective and right on target. Reformulation of future sanctions must show an indication of the feasibility of the perpetrator and should mention what are the indicators of perpetrators who can be subject to rehabilitation and what form of rehabilitation in order to provide legal certainty.